URBAN-RURAL COMPARISONS OF ATTITUDE TOWARDS MENTAL ILLNESS AMONGST HEALTHCARE UNIVERSITY STUDENTS - Abro, Arbaz Gul; Muhammad Aliyan Ahmed; Mahrukh Abro; Abdul Sami; Tariq Feroz (Journal of Pakistan Psychiatric Society, 2024)
Abstract: Objective: To examine and compare the differences in attitudes of healthcare university students towards mental illness from urban and rural backgrounds. Design: Cross-sectional study Place and duration of study: Study was conducted at Liaquat University of Medical & Health Sciences Jamshoro, Sindh from October to December 2023. Methods: Sampling population were undergraduate students registered in different undergraduate healthcare programs (MBBS, BDS, DPT, Pharmacy, Nursing, Biomedical Engineering, BS MLT, BSRT, BS Forensic Chemistry/Biology and other allied departments), aged 18-27 years, of either gender, gave their consent of participation were included in the study. Data was collected with the help of online questionnaire. Mental Illness Clinician Attitude Scale (MICA-2 and 4) were employed to assess the healthcare student’s attitude towards mental illness. Results: There was female preponderance and mean age of subjects was 21.38 years ± SD 1.689. Majority of students were from MBBS and studying in final year and belonged to rural areas. The Median MICA score was 52. There was significant difference between scores of rural and urban students and statistically significant difference was noted among students from different departments and academic years. Conclusion: Overall attitude of healthcare university undergraduate students towards mental health illness is unsatisfactory. Whereas, the students from rural areas had poor attitude towards mental illness compared with those from the urban areas.